Analyzing the Usage of Noun Phrases on Billboard Advertisements - Sofyan, Nurlaily; Hasidi, Syara M.; Umasugi, Faujia; Wahid, Jusmin H.J. (International Journal of Education, Information Technology, and Others, 2024)
Abstract There are many varieties of advertisement, and one of them is billboard. The usage of language on the billboard requires a short message but the meaning is easily understood by consumers. It aims to encourage consumers to buy the products offered. So, the function of language is used to promote goods, and it is also be useful for learners to analyze its language as well as meaning. The purpose of this study is to know the usage of noun phrase on billboards advertisement. The type of research used is qualitative. The object of this research is advertisement boards. Data collection technique is done by choosing billboard images randomly. While, data analysis technique used 3 steps, they are: settle the data obtained, and then apply it in the research result and discussion. The final activity is to analyze data based on the usage of noun phrases on the billboard. From the results of 15 billboards that have been chosen, it can be conclude that not all the language used in the advertisement is in the form of phrases. It is also in the form of sentences. Even, there is a combination between sentence and a phrase in one advertisement. Data prooved that there are 8 advertisements of billboard included in noun phrase. 2 advertisements involved in adjective phrase. And, there are 2 advertisements are categorized as verb phrase. Finally, the others are in the form of sentences. The result of this research can be the additional references for the students in studying about grammar, syntax or even semantics in the university level. Keywords: Usage, Noun Phrases, Advertisement, Billboard